UTILIZATION OF ECO ENZYME FOR ORGANIC WASTE MANAGEMENT AND PLANT CARE IN SUSTAINABLE AGRICULTURE IN TEMBELING VILLAGE - Dwi Septi Haryani; Sri Langgeng Ratnasari; Ranti Utami; Mita Elvira; Fenny Fenny; Anggia Sekar Putri; Selvi Fauzar; Niken Dwi Agustina (MINDA BAHARU, 2026)
This community service program aimed to improve farmers’ knowledge and skills regarding the utilization of Eco Enzyme as a solution for organic waste management and as a supporting agent for plant care in Tembeling Village. The main challenges faced by the local farming community were the continued dependence on chemical fertilizers and pesticides, as well as the underutilization of organic waste. The program was conducted through socialization, training, hands-on Eco Enzyme production, mentoring, and evaluation. The results showed that participants were able to understand the Eco Enzyme production process, convert organic waste into a valuable fermented product, and apply it as a natural pest repellent and a supporting agent for plant care. In addition, the program increased farmers' awareness of the importance of organic waste management and environmentally friendly agricultural practices. This program is expected to encourage farmers to adopt simple waste-based technologies as part of sustainable agriculture.